2019
DOI: 10.1111/1475-6773.13109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of administration mode onCAHPSsurvey response rates and results: A comparison of mail and web‐based approaches

Abstract: Objective The objective of this study was to compare response rates, respondents' characteristics, and substantive results for CAHPS surveys administered using web and mail protocols. Data Sources Patients who had one or more primary care visits in the preceding 6 months. Study Design/Data Collection Methods Patients for whom primary care practices had email addresses were randomized to one of four survey administration protocols: web via a portal invitation; web via an email invitation; combination of web and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 14 publications
5
38
0
Order By: Relevance
“…The results are consistent with a number of previous studies reporting that mail surveys achieve higher response rates than electronic and web-based approaches. [2][3][4][5][6][7][8][9][10][11] A recent Consumer Assessment of Healthcare Providers and Systems survey produced similar results when comparing protocols based on web responses via an email invitation and mail. 7 The mail protocol yielded more than twice the response rate of the web approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results are consistent with a number of previous studies reporting that mail surveys achieve higher response rates than electronic and web-based approaches. [2][3][4][5][6][7][8][9][10][11] A recent Consumer Assessment of Healthcare Providers and Systems survey produced similar results when comparing protocols based on web responses via an email invitation and mail. 7 The mail protocol yielded more than twice the response rate of the web approach.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of background characteristics reported in the literature are inconsistent. [2][3][4][5][6][7][8][9][10] The results from two previous randomised studies showed similar background characteristics for respondents in different randomised groups. 2 3 However, the respondents in those surveys were all contacted by mail.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of different methods of using web portals for surveying consumers about their experience with medical care revealed that response rates were higher for mail questionnaires, compared with web-based protocols. 6 A study on physicians 7 found that initial mailing of questionnaire followed by web surveying non-responders increased response rates and enhanced the representativeness of the sample. For surveys with shorter time frame, the reverse method, namely initial web survey followed by mailing the questionnaire to non-responders was recommended, though key outcome variables did not differ between these data collection methods.…”
mentioning
confidence: 99%